2015
DOI: 10.1007/s10461-015-1024-z
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity is Associated with Better Neurocognitive and Everyday Functioning Among Older Adults with HIV Disease

Abstract: We examined the association between physical activity (PA), neurocognitive impairment (NCI), and instrumental activities of daily living (IADLs) among older HIV+ persons. One hundred older HIV+ adults completed the International Physical Activity Questionnaire (IPAQ), a neurocognitive battery, and IADL scale. Higher levels of moderate PA were associated with lower odds of NCI (p=0.01), even when covariates were modeled. The association between moderate PA and NCI was driven by executive function (p=0.04). High… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
42
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 55 publications
4
42
2
1
Order By: Relevance
“…In a cross-sectional study of 335 adults with HIV, Dufour and colleagues (2013) found that those who exercised were less likely to have neurocognitive impairment compared to those who did not exercise (odds ratio = 2.63, p < 0.05). Similar findings have been found in older adults with HIV (Fazeli et al, 2015). …”
Section: Lifestyle Factors Brain Health and Cognitionsupporting
confidence: 89%
“…In a cross-sectional study of 335 adults with HIV, Dufour and colleagues (2013) found that those who exercised were less likely to have neurocognitive impairment compared to those who did not exercise (odds ratio = 2.63, p < 0.05). Similar findings have been found in older adults with HIV (Fazeli et al, 2015). …”
Section: Lifestyle Factors Brain Health and Cognitionsupporting
confidence: 89%
“…Moreover, work by our group among older adults living with HIV has shown that active lifestyles (including PA) are associated with better cognition and that PA is associated with better cognition and everyday functioning among older adults living with HIV [39,40]. Neuroimaging work has recently revealed that those who are physically active, as opposed to sedentary, have better executive functioning scores, and executive functioning was significantly associated with larger putamen volumes in adjusted models [40,41].…”
mentioning
confidence: 87%
“…For example, increasing physical activity by as little as 500 steps per day improves performance in older adults on measures such as the Trail Making Test B (Rosenberg et al, 2012). A recent cross-sectional study indicated that PLWH with neurocognitive impairment ( n = 43) exhibited significantly less moderate physical activity (weekly minutes of moderate-intensity physical activity reported on the International Physical Activity Questionnaire) compared to cognitively intact PLWH ( n = 57; Fazeli et al, 2015); however, the effect of a physical activity intervention on HAND has not been assessed. In addition, physical activity interventions applied in the HIV population have typically required rigorous activity (e.g., running on a treadmill; O’Brien, Nixon, Tynan, & Glazier, 2010) and significant participant effort (traveling to a gym several times a week), which may not be feasible for many individuals.…”
mentioning
confidence: 99%